Calcium signalling in medial intercalated cell dendrites and spines. (16th July 2017) - Strobel, Cornelia; Sullivan, Robert K. P.; Stratton, Peter; Sah, Pankaj
Abstract : Key points: Dendritic and spine calcium imaging in combination with electrophysiology in acute slices revealed that in medial intercalated cells of the amygdala: Action potentials back‐propagate into the dendritic tree, but due to the presence of voltage‐dependent potassium channels, probably Kv4.2 channels, attenuate over distance. A mixed population of AMPA receptors with rectifying and linear I–V relations are present at individual spines of a single neuron. Decay kinetics and pharmacology suggest tri‐heteromeric NMDA receptors at basolateral–intercalated cell synapses. NMDA receptors are the main contributors to spine calcium entry in response to synaptic stimulation. Calcium signals in response to low‐ and high‐frequency stimulation, and in combination with spontaneous action potentials are locally restricted to the vicinity of active spines. Together, these data show that calcium signalling in these GABAergic neurons is tightly controlled and acts as a local signal. Abstract: The amygdala plays a central role in fear conditioning and extinction. The medial intercalated (mITC) neurons are GABAergic cell clusters interspaced between the basolateral (BLA) and central amygdala (CeA). These neurons are thought to play a key role in fear and extinction, controlling the output of the CeA by feed‐forward inhibition. BLA to mITC cell inputs are thought to undergo synaptic plasticity, a mechanism underlying learning, which is mediated by NMDA receptor‐dependent mechanisms that require changes in cytosolic calcium. Here, we studied the electrical and calcium signalling properties of mITC neurons in GAD67‐eGFP mice using whole‐cell patch clamp recordings and two‐photon calcium imaging. We show that action potentials back‐propagate (bAP) into dendrites, and evoke calcium transients in both the shaft and the dendritic spine. However, bAP‐mediated calcium rises in the dendrites attenuate with distance due to shunting by voltage‐gated potassium channels. Glutamatergic inputs make dual component synapses on spines. At these synapses, postsynaptic AMPA receptors can have linear or rectifying I–V relationships, indicating that some synapses express GluA2‐lacking AMPA receptors. Synaptic NMDA receptors had intermediate decay kinetics, and were only partly blocked by GuN2B selective blockers, indicating these receptors are GluN1/GluN2A/GluN2B trimers. Low‐ or high‐frequency synaptic stimulation raised spine calcium, mediated by calcium influx via NMDA receptors, was locally restricted and did not invade neighbouring spines. Our results show that in mITC neurons, postsynaptic calcium is tightly controlled, and acts as a local signal. Key points: Dendritic and spine calcium imaging in combination with electrophysiology in acute slices revealed that in medial intercalated cells of the amygdala: Action potentials back‐propagate into the dendritic tree, but due to the presence of voltage‐dependent potassium channels, probably Kv4.2 channels, attenuate over distance. A mixed population of AMPA receptors with rectifying and linear I–V relations are present at individual spines of a single neuron. Decay kinetics and pharmacology suggest tri‐heteromeric NMDA receptors at basolateral–intercalated cell synapses. NMDA receptors are the main contributors to spine calcium entry in response to synaptic stimulation. Calcium signals in response to low‐ and high‐frequency stimulation, and in combination with spontaneous action potentials are locally restricted to the vicinity of active spines. Together, these data show that calcium signalling in these GABAergic neurons is tightly controlled and acts as a local signal.